LPTO-01. LEPTOMENINGEAL METASTASIS FROM OVARIAN CARCINOMA TREATED WITH SYSTEMIC HIGH-DOSE METHOTREXATE. (12th August 2019) - Coffee, Elizabeth; Lobbous, Mina; Nabors, L Burt
Abstract: BACKGROUND: Central nervous system metastasis in ovarian cancer is reported in approximately 1% of cases and typically localizes to the parenchyma. Leptomeningeal disease (LMD) is exceedingly rare. Prognosis is extremely poor with median survival of 60 days. Given the rarity of LMD in ovarian cancers, there is no consensus on the optimal treatment approach. High-dose systemic methotrexate (HD-MTX) has been studied in LMD. CASE REPORT: A 41-year-old Caucasian woman with a history of BRCA-positive stage IIIC ovarian carcinoma who was treated with cytoreduction and multiple rounds of intravenous and intraperitoneal chemotherapy presented to the emergency room with progressive headaches, vomiting and neck pain. Contrasted MRI of the brain showed nodular enhancement along the cerebellar folia, concerning for leptomeningeal disease. Cerebrospinal fluid cytology analysis was positive for malignancy and she was diagnosed with leptomeningeal metastasis 2.5 years after her diagnosis with ovarian carcinoma. Induction therapy with systemic HD-MTX was given every other week and complete response was achieved after two induction cycles. Serum CA-125 level decreased from 565.7 U/mL (prior to treatment) to 50.4 U/ML after the sixth induction cycle and she was transitioned to maintenance HD-MTX. Approximately 6 months after initiation of HD-MTX, contrasted MRI demonstrated LMD recurrence with corresponding rise in CA-125 to 395 U/mL. Whole body CT imaging did not show local disease recurrence. Temozolomide was added to the HD-MTX regimen and craniospinal radiation therapy was planned but her neurologic condition continued to decline. She died 8 months after her diagnosis of LMD. CONCLUSION: LMD has a dismal prognosis. HD-MTX may prolong the overall survival in patients with LMD secondary to ovarian carcinoma. In these patients, serum CA-125 level may serve as a biomarker for monitoring CNS disease burden. Due to the rarity of LMD, multi-institutional prospective studies are needed to explore novel therapeutics in LMD.